PERANAN PEMBELAJARAN MATA KULIAH BAHASA ARAB PADA KEMAMPUAN MENULIS BERBAHASA ARAB BAGI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA ARAB (PBA) ANGKATAN 2009 JURUSAN TARBIYAH STAIN PEKALONGAN - Ali Burhan; Abdul Muíin; Abdul Basith (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
This study focused on the role of Arabic teaching in increasing academic writing skill of the students of 2009 who were studying at Arabic Teaching Program of STAIN Pekalongan. The result showed that most of them (60%) declared not ready to write their minithesis in Arabic. They were not enough well-prepared in Arabic academic writing. Their grades in overall Arabic subject were 68 in range 0–100: starting at General Arabic (Arabic I, II, and III); structure (nahwu and Sharf), pronounciation (Qir‚-ah), listening (Istim‚í), speaking (Kal‚m), up to writing skill (kit‚bah). It verified that student who had a good grade in a lingual subject, like Arabics, is not equal with his language skill, especially in writing skill.